Biophysical aspects of cardiac muscle : proceedings of the Cardiac Muscle Symposium, May 14-16, 1977, Shiraz, Iran - Morad, Martin; Tabatabai, Mahmood (Academic Press, 1978)
Biophysical Aspects of Cardiac Muscle.